Application Of Good And Correct Hands Washing In The Effort To Prevent Covid-19 In The Community Of Paas Pameungpeuk Village, Garut - Intan Permana; Anggieta Wian Rahmadani; Aulia Saputri Maharani; Riska Habibah Utama; Siti Hojar (Fakultas Kewirausahaan Universitas Garut, 2022)
Abstract The corona virus or known as Covid-19 (Corona Virus Desese-2019) is a pandemic that occurs in various parts of the world, this virus has characteristics with a high speed of spread which is aform of public concern, However it can be prevented by many ways to prevent the transmission of covid-19, one of which is to maintain cleansliess such as washing hands properly. The purpose of this activity is to increase of washing hands properly and properly in preventing Covid-19, especially for children who take part in teaching and learning activities and posyandu activities to appy health protocols, especially to get used to washing their hands before and after doing activities. The method of implementing this activity is by conducting a field survey, especially in Paas Village, starting from providing education on how to wash hands properly and properly showing how to make hand washing soap from bar soap, providing hand washing facilities which are divided into the mosque At-Tayyibah. Furthmore, carrying out activities implementing health protocols to the community by carrying out this activity, the village community starts to get used to washing their hands before and after doing the activity. Abstrak Virus corona atau yang dikenal dengan COVID-19 (Corona Virus Desese-2019) merupakan pandemi yang terjadi di berbagai belahan dunia. Virus ini memiliki karakteristik dengan kecepatan penyebaran yang tinggi, yang menjadi salah satu bentuk kekhawatiran masyarakat, namun bisa dicegah dengan berbagai hal. Banyak cara untuk mencegah penularan Covid-19 ini, salah satunya adalah dengan menjaga kebersihan seperti mencuci tangan yang baik dan benar. Tujuan kegiatan ini adalah untuk meningkatkan kesadaran masyarakat tentang pentingnya mencuci tangan yang baik dan benar dalam pencegahan Covid-19, khususnya bagi anak-anak yang mengikuti kegiatan belajar mengajar dan kegiatan posyandu agar menerapkan protokol kesehatan khususnya membiasakan mencuci tangan sebelum dan sesudah melakukan aktivitas. Metode pelaksanaan kegiatan ini dengan melakukan survei lapangan khususnya di Desa Paas, dimulai dari pemberian edukasi cara mencuci tangan yang baik dan benar, menunjukkan cara membuat sabun cuci tangan dari sabun batangan, memberikan sarana tempat cuci tangan yang di bagi ke Masjid At-Tayyibah selanjutnya melakukan kegiatan penerapan protokol kesehatan kepada masyarakat. Dengan dilaksanakannya kegiatan ini, masyarakat Desa Paas mulai membiasakan diri mencuci tangan sebelum dan sesudah melakukan aktivitas.